The timing and structure of the 8.2 ka event revealed through high-resolution speleothem records from northwestern Madagascar. (15th September 2021) - Duan, Pengzhen; Li, Hanying; Sinha, Ashish; Voarintsoa, Ny Riavo G.; Kathayat, Gayatri; Hu, Peng; Zhang, Haiwei; Ning, Youfeng; Cheng, Hai
Abstract: Although the 8.2 ka event is a well-known globally documented abrupt climate event, its detailed expression in tropical southeastern Africa is poorly constrained. Here we present a high resolution and precisely dated record of the regional hydroclimatic variability between 8.5–7.5 ka BP from a polymorphic speleothem (ABC-1) from northwestern Madagascar. In combination with the exclusive recurrences of calcite layers (indicative of wetter conditions), the distinctly negative excursions in the ABC-1 δ 18 O record manifest a wet 8.2 ka event that spanned from 8.230 to 8.053 ka BP. The event is characterized by the replacement of shorter-term (interannual to interdecadal) δ 18 O-δ 13 C coherence with the longer-term (multidecadal to centennial) coherence, suggesting a stable and well-developed forest system during the 8.2 ka event. Our data reveal a two-stage structure of the 8.2 ka event, which is superimposed with two brief pluvial episodes in each stage. The widely documented two peaks/troughs during Stage-I suggest rapid propagation of climate signal through atmospheric processes triggered initially by the freshwater forcing, whereas the divergent behaviors of the peaks/troughs in Stage-II in different climate systems may suggest a different forcing. Highlights: Exclusively episodic deposition of the calcite layers and lower speleothem δ 18 O manifest a wet 8.2 ka event in NW Madagascar. The 8.2 ka event in NW Madagascar exhibits a two-stage structure with each stage superimposed by two severe pluvial episodes. The timescale variation of coherence between δ 18 O and δ 13 C indicates the resilience of the ecosystem to climate change.